Evaluation of the hepatoprotective effect of naringenin loaded nanoparticles against acetaminophen overdose toxicity. (31st December 2022) - Lu, Ruijie; Yu, Run-Jie; Yang, Chunhui; Wang, Qian; Xuan, Yunxia; Wang, Zeqing; He, Zhimin; Xu, Yan; Kou, Longfa; Zhao, Ying-Zheng; Yao, Qing; Xu, Shi-Hao
Abstract: Acute liver injury is a common clinical disease, which easily leads to liver failure and endangers life, seriously threatening human health. Naringenin is a natural flavonoid that holds therapeutic potential against various liver injuries; however it has poor water solubility and bioavailability. In this study, we aimed to develop naringenin-loaded bovine serum albumin nanoparticles (NGNPs) and to evaluate their hepatoprotective effect and underlying mechanisms against acetaminophen overdose toxicity. In vitro data indicated that NGNPs significantly increased the drug solubility and also more effectively protected the hepatocyte cells from oxidative damage during hydrogen peroxide exposure or lipopolysaccharide (LPS) stimulation. In vivo results confirmed that NGNPs showed an enhanced accumulation in the liver tissue. In the murine model of acetaminophen-induced hepatotoxicity, NGNPs could effectively alleviate the progression of acute liver injury by reducing drug overdose-induced levels of oxidative stress, inflammation and apoptosis in hepatocytes. In conclusion, NGNPs has strong hepatoprotective effects against acetaminophen induced acute liver injury.